IMPLIKASI PEMBAGIAN HARTA BERSAMA ATAS OBJEK YANG MASIH DALAM STATUS KREDIT (KPR) PASCA PERCERAIAN - Najwa Aulia Nabila; Fitria Agustin (CV. Denasya Smart Publisher, 2026)
Disputes over joint property in the form of an outstanding mortgage often give rise to legal complexities at the intersection of family law and security law. This study aims to analyze the legal status and mechanisms for the division of mortgage properties following divorce, as well as the legal implications regarding the bank’s position as a preferred creditor. The research method employed is normative legal analysis using a statutory approach and a review of judicial decisions. The results of the study indicate that the mortgage property constitutes joint property encompassing both assets and liabilities, where its division cannot be separated from the remaining debt and the attached security rights. Based on SEMA No. 3 of 2018, a claim regarding joint property involving an asset still under mortgage without involving the bank will be declared “Not Acceptable” (Niet Ontvankelijk Verklaard). In conclusion, judges must apply the “Net Value” approach in adjudicating cases to ensure justice for former spouses without infringing upon the bank’s right of preference. Synchronization through subjective novation or the bank’s involvement as a Co-Defendant is an absolute requirement to ensure the judgment is enforceable and does not pose a risk of non-performing loans.